Meta-Analysis to Determine Normative Values for the Special Judo Fitness Test in Male Athletes: 20+ Years of Sport-Specific Data and the Lasting Legacy of Stanisław Sterkowicz - Katarzyna Sterkowicz-Przybycień; David H. Fukuda; Emerson Franchini (MDPI AG, 2019)
The aim of this study was to evaluate Special Judo Fitness Test (SJFT) results specific to the population of male judoka and to develop age category norms for junior and senior athletes. A systematic review of the existing literature was conducted to identify 281 publications reporting SJFT results between 1995 and 2018. The final meta-analysis included data from 37 relevant studies that reported SJFT results from 51 individual samples of 515 senior and 209 junior male athletes. The combined mean and SD for SJFT variables were calculated, and the Cohen’s d effect size with 95% confidence intervals (CI) for the senior and junior age classifications were compared. Senior athletes demonstrated higher total number of throws (d = 0.41, CI = 0.25−0.57, p <0.001) and heart rate (HR) immediately after the SJFT (d = 0.18, CI = 0.02−0.35, p = 0.025) with limited differences for HR one minute after the SJFT between groups. The SJFT index was lower for seniors compared to juniors (d = 0.38, CI = 0.22−0.54, p <0.001) indicating better overall performance by the more advanced athletes. Percentile rankings were used to develop SJFT classificatory tables for male senior and junior judo athletes. Training staff can use the age group classifications in the evaluation process of their athletes and for the purpose of monitoring training.